Mathematical model of diesel engine characteristics for determining the performance of traction dynamics of wheel-type tractor - Rebrov, O. Yu.; Kozhushko, A. P.; Kalchenko, B. I.; Mamontov, A. G.; Zakovorotniy, A.; Kalinin, E.; Holovina, E. (Scientific Route OÜ, Estonia, 2020)
Wheel-type tractors carry out a range of processing operations, with the exception of early spring work, when caterpillar tractors are used to reduce the compaction effect on the soil. Therefore, to plan the costs and reserves associated with fuel consumption, it is necessary to have an estimate of the fuel economy of the tractor in basic agricultural operations. An objective assessment of fuel consumption requires a mathematical model that describes the fuel characteristics of the engine, taking into account the speed and load torque in a wide range of variation. Verification of the model is possible only with experimental data. Since the efficiency and fuel economy of a tractor depends not only on engine performance, but also on the perfection of the transmission, the running system and the rational choice of speed, it is necessary to take into account the time-varying nature of the tractor’s traction load. The complex of agricultural operations can be divided into characteristic cycles of load change over time. This principle is the basis of PowerMix test cycles, which are conducted on a concrete track to ensure repeatability of the experiment. The use of the variable load on the tractor in the PowerMix tests is positive, but in actual field tests the results may differ due to the instability of the soil properties. On the other hand, PowerMix field cycles can be taken as standard test loads in the simulation of tractor traction tests on the ground.
Keywords: diesel engine; specific fuel consumption; approximation; fuel efficiency; PowerMix test cycles